Diastereoselective formation of homochiral flexible perylene bisimide cyclophanes and their hybrids with fullerenes - Solymosi, Iris; Krishna, Swathi; Nuin, Edurne; Maid, Harald; Scholz, Barbara; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Hirsch, Andreas (Chemical Science, 2021)
Cyclophanes of different ring sizes featuring perylene-3,4:9,10-tetracarboxylic acid bisimide (PBI) linked by flexible malonates were designed, synthesized, and investigated with respect to their structural, chemical and photo-physical properties. It is predominantly the number of PBIs and their geometric arrangement, which influence dramatically their properties. For example, two-PBI containing cyclophanes reveal physico-chemical characteristics that are governed by strong co-facial π–π interactions. This is in stark contrast to cyclophanes with either three or four PBIs. Key to co-facial π–π stackings are the flexible malonate linkers, which, in turn, set up the ways and means for diastereoselectivity of the homochiral PBIs at low temperatures, on one hand. In terms of selectivity, diastereomeric (M,M)/(P,P) : (M,P)/(P,M) pairs with a ratio of approximately 10 : 1 are discernible in the 1H NMR spectra in C2D2Cl4 and a complete diastereomeric excess is found in CD2Cl2. On the other hand, symmetry-breaking charge transfer as well as charge separation at room temperature are corroborated in steady-state and time-resolved photo-physical investigations. Less favourable are co-facial π–π stackings in the three-PBI containing cyclophanes. For statistical reasons, the diastereoisomers (M,M,M)/(P,P,P) and (M,M,P)/(P,P,M) occur here in a ratio of 1 : 3. In this case, symmetry-breaking charge transfer as well as charge separation are both slowed down. The work was rounded-off by integrating next to the PBIs, for the first time, hydrophobic or hydrophilic fullerenes into the resulting cyclophanes. Our novel fullerene–PBI cyclophanes reveal unprecedented diastereoselective formation of homochiral (M,M)/(P,P) pairs exceeding the traditional host–guest approach. Hybridization with fullerenes allows us to modulate the resulting solubility, stacking, cavity and chirality, which is of tremendous interest in the fiel
CRIS-Team WoS Importer:2021-10-29